Surgical management of a retrohepatic inferior vena cava injury following blunt abdominal trauma - Stephen J. Fenton; Thane A. Blinman; Robin C. Cook; Joy L. Collins (Elsevier, 2014)
The clinical scenario of a 3 year-old child who sustained a retrohepatic inferior vena cava injury following blunt abdominal trauma is reported. The presentation, evaluation, and surgical management are discussed.